The Application of Article 53 of KHI (Islamic Law Compilation) Regarding Pregnant Marriage in Lottery Marriage - Neng Eri Sofiana; Muhammad Ismail Sunni (IAIN Manado, 2021)
Pregnant marriagebecomes a phenomenon that is still happening in Indonesia and is even one of the most significant contributors to the reason for the dispensation of marriage. In Parangdistrict, Magetan Regency, pregnant marriage is also one of the solutionsfor a case in which many women get pregnant without a legal marriage. Pregnancies were not initiated from sexual intercourse between a man and a woman but were carried out by many men, so the model of determination was by lottery. Furthermore, this article will analyze the pregnant woman who is married to a man who does not impregnate her and the child's status according to article 53 of KHI. In article 53 KHI, no line explicitly explains the permissibility or prohibition of a pregnant woman to marry a man who does not impregnate her. Still, many interpret that this is not allowed.Meanwhile, a legitimate child in KHI is a child born during a legal bond. So, when DNA testing proof or the like is not done to see the legality of the child, then this child is still considered a legitimate child by both of them because they were born in a marriage bond. In sum, a pregnant marriage in a lottery marriage with a man who does not impregnate the woman has many sides of ambiguity. So, there must be a revision of article 53 and article 99 of KHI.